Strategi Komunikasi Politik Adik Sepupu Gus Baha’ Dalam Kontestasi Politik Desa (Telaah atas Kemenangan Adik Sepupu Gus Baha’ dalam Pemilihan Kepala Desa Narukan Rembang Tahun 2022) - Mohammad Ilham Akbar; Imam Safi’I (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The 2022 Narukan Village Head Election in Rembang gained significant public attention because one of the candidates was the cousin of the well-known cleric Gus Baha’. Many assumed that his victory was due to the strong influence of Gus Baha’s religious image. This study aims to analyze the political communication strategies used by the candidate to win the election. The study employs a descriptive qualitative approach using observation, interviews, and documentation. The findings reveal that the candidate’s victory was influenced not merely by kinship or religious image but also by the effective implementation of emotional and spiritual communication strategies. Emotional approaches included empathy and social similarity, while the spiritual approach reflected religious representation and integrity, creating public trust amid prevalent money politics.